1983
DOI: 10.1093/bja/55.11.1107
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Disposition in Children and Adults

Abstract: The pharmacokinetics of ketamine 2 mg kg-1 i.v. and 6 mg kg-1 i.m. were investigated in nine children undergoing minor surgery. After either route of administration plasma ketamine concentrations were similar to those found in adult patients receiving the same dose, except at later times after i.v. injection, when concentrations were smaller in children. Also, absorption after i.m. injection appeared to be more rapid in children. Substantially larger concentrations of the metabolite norketamine were found in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(78 citation statements)
references
References 0 publications
8
69
0
1
Order By: Relevance
“…Administration of neither 25, 50, nor 100 M ketamine was cytotoxic to HepG2 cells. Concentrations of ketamine used in this study are within the range of clinical relevance (Domino et al, 1982;Grant et al, 1983). Under such clinically relevant concentrations, ketamine suppressed polymerization of F-actin and microtubular cytoskeletons.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Administration of neither 25, 50, nor 100 M ketamine was cytotoxic to HepG2 cells. Concentrations of ketamine used in this study are within the range of clinical relevance (Domino et al, 1982;Grant et al, 1983). Under such clinically relevant concentrations, ketamine suppressed polymerization of F-actin and microtubular cytoskeletons.…”
Section: Discussionmentioning
confidence: 98%
“…Ketamine was dissolved in phosphate-buffered saline (0.14 M NaCl, 2.6 mM KCl, 8 mM Na 2 HPO 4 , and 1.5 mM KH 2 PO 4 ). Concentrations of ketamine (Յ100 M), which correspond to clinical plasma concentrations (Domino et al, 1982;Grant et al, 1983), were chosen as the treated dosages in this study. To avoid drug interaction, when HepG2 cells were exposed to ketamine, the culture medium did not contain serum and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…However, the findings that the concentrations at which ketamine inhibits the NMDA receptors are about 10-fold lower than the plasma concentrations needed to induce anesthesia in mammals have suggested that inhibition of NMDA receptors may not be the only determinant of dissociative anesthesia (Grant et al, 1983;Coan and Collingridge, 1987). Studies investigating the sensitivity of numerous ligand-gated channels ectopically expressed in different systems to these compounds came to demonstrate that ␣7 nAChRs as well as ␤4* and ␤2* nAChRs can be inhibited noncompetitively and voltage dependently by ketamine and MK-801 (Ramoa et al, 1990;Buisson and Bertrand, 1998;Furuya et al, 1999).…”
Section: Anesthetics and Psychotomimetics Interact With Neuronal Nachmentioning
confidence: 99%
“…No psychological sequelae were observed in our patient, possibly because of the co-administration of midazolam (Park et al, 1987). Grant et al (1983) reported a greater plasma clearance of ketamine in children aged 4-9 years than in adults (16.8 and 12.6 ml min-' kg-', respectively). They also found greater plasma norketamine concentrations in children than in adults suggesting that the N-demethylation of ketamine to norketamine is the major metabolic pathway in children.…”
Section: Discussionmentioning
confidence: 44%
“…Its major metabolite is norketamine which animal studies suggest is pharmacologically active (White et al, 1982). There have been few studies of the pharmacokinetics of ketamine in children (Cook et al, 1982;Grant et al, 1983). It is well known that thermal injury causes 'resistance' to many drugs used in anaesthetic practice (Marathe et al, 1989;Martyn, 1986;White et al, 1982) Total parenteral nutrition (glucose, aminoacids and fat) and albumin were given from day 2 (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%